THE METHODICS OF SIGNAL TYPE IDENTIFICATION ACCURACY WITH HARDWARE TOOLS - Kharchenko, Volodymyr; Larin, Vitaliy; Savitskaya, Iana (Proceedings of National Aviation University (archive), 2014)
The error fractions analysis of receiving tract devices that influence on the signal type identificationaccuracy is given in the article. To increase the signal type identification accuracy with hardware tools the errorfractions of electronic devices are determined.